Diseño y modelización de programas para la vivienda de interés social, complejidades y consecuencias en su aplicación, el caso cuenca Matanza Riachuelo - Sanmiguel, Damián Enrique (2015)
Studies on the implementation of housing policies rarely focus on the bureaucratic dimension. Bureaucracy that, in the imaginary of society, is responsible for the inefficiency with which the State is usually branded.\nThis work was proposed to analyze the processes that are manifested in the formulation, presentation, evaluation, approval, execution and follow-up of projects of housing solutions financed from the National State for villas and precarious settlements, in relation to the "Mendoza Cause".\nInfrastructure works, urban equipment, housing, housing improvements and complementary works for the improvement of the habitat are interventions generally proposed and designed by municipal and/or provincial organizations and financed by the National State.\nWe have verified, from our respective professional, bureaucratic and academic practices, that the knowledge of the academy, the State and the territory, the latter understood as the space of the recipients, must coexist in the diagnostic stages and in their respective proposals. of intervention, generating link methodologies between these three types of knowledge and actively participating in the necessary mechanisms in decision-making.\nWe can also affirm that for a fragment of the city to strengthen, remedy or mitigate any dysfunction related to habitat problems, it is necessary that "management" be understood as a participatory and comprehensive process, in which all the actors involved can express and assert their interests, turning it into an associated management, perhaps a legacy of that Situated Strategic Planning.\nIn these processes, the relationship between the national, provincial and municipal governments based on their responsibilities, duties and rights is crucial and defining in each of the stages.\nIt is the relationship between state jurisdictions that makes it possible for these works to materialize. And that interjurisdictional relationship is based on their administrations and these, in turn, associated with the notion of "bureaucracy", an unavoidable vehicle for the management and realization of any Plan or Project.\nWhen one thinks of an effective, efficient and effective State, the relationship between that State and its bureaucratic apparatus is questioned, among other things. Without fear of being wrong, we can affirm that the success in the formulation and execution of Plans and Programs promoted and financed by the National State depends to a great extent on the administrative soundness of the State itself. And this administrative solidity has its roots in the much-beaten "state bureaucracy" that is often understood as an insurmountable barrier for the community, conspiring in the processes of habitat improvement and social integration.\nIn addition, a complement is added from the perspective of disciplinary training, and tries to challenge it in an administrative key. The presence of architects in multiple municipal, provincial or national agencies and areas with specific responsibilities in decision-making is a recurring indicator of the need to rethink the role of the discipline at the service of the State.\nAdherence to norms and standardization does not seem to be in the DNA of a disciplinary training that, almost like a universal mandate, appeals to constant creativity and manipulation of the material world. And although the bureaucratic field and the disciplinary field seem to collide in public offices, this work tries to find a way out.